PEMANFAATAN SOLID EX-DECANTER DALAM PEMBUATAN ROTI SOLID DENGAN TAMBAHAN ONGGOK SEBAGAI PAKAN TERNAK RUMINANSIA - Munthe, Mandala Putra; Purwanto, Heri; Giyanto, Giyanto (Jurnal Agro Fabrica, 2022)
Solid bread is ruminant feed made from solid ex-decanter that has gone through a mixing process with local ingredients and has been molded into a circle so that it looks like bread and is referred to as solid bread. This study uses experimental methods. Consists of 3 levels of treatment, namely: without fermentation, 7 days of fermentation, and 14 days of solid fermentation using EM-4. The addition of local ingredients, namely cassava (onggok), palm kernel meal, molasses, salt, and lime can help the nutritional content of solid bread to conform to the Indonesian National Standard (SNI). The parameters tested in this study were: crude protein (PK), crude fat (LK), crude fiber (SK), ash, calcium (Ca), phosphorus (P), and water. Unfermented solid bread contains 14.05% crude protein, 9.23% crude fat, 20.46% crude fiber, 5.10% ash, 0.8097% calcium, 0.744% phosphorus, 8.17% water. The 7-day fermented solid bread contains 22.79% crude protein, 8.04% crude fat, 12.27% crude fiber, 4.20% ash, 0.8931% calcium, 0.794% phosphorus, 8.98% water. Fermented solid bread for 14 days contains 28.20% crude protein, 7.87% crude fat, 9.32% crude fiber, 3.82% ash, 0.9378% calcium, 0.829% phosphorus, 9.56% water. The results of this study indicate that several treatments, namely non-fermented, fermented for 7 days, fermented for 14 days, and some of the nutritional content of solid bread have met SNI. Crude protein, crude fiber, ash, calcium, and water content meet SNI but some do not meet SNI such as crude fat, and phosphorus in 7-day fermentation and 14-day fermentation. In non-fermentation, phosphorus has met SNI.